Determination of October to December Seasonal Rainfall Variability, its Seasonal Onset and Cessation Dates in Zanzibar, Tanzania - Suleiman, Riziki Ali; Wen, Wang; Kazora, Jonah; Lipiki, Elias Julius (Journal of Sustainability and Environmental Management, 2023)
This study aimed in determining the October to December (OND) rainfall variability, seasonal onset and cessation dates in Zanzibar, Tanzania. The study used 10 years daily rainfall (2012–2021) and 30 years monthly rainfall datasets obtained from six meteorological stations. Other climate parameters of Sea Surface Temperature (SST), Winds, Relative Humidity and Vertical Velocity having temporal resolution of 30 years (1992-2021) were also used. Rainfall seasonal variability was analyzed using Climatological mean and Empirical Orthogonal Function (EOF) analysis, onset and cessation dates was calculated using Cumulative percentage anomalies. The composite analysis was taken to examine the atmospheric circulation anomalies associated with OND seasonal rainfall. The study revealed that; OND season is characterized by normal to moderate rainfall variations from region to region with its peak marked at November (mid-season). Despite the slight differences over both Islands, average onset dates occur on third dekade of October (22nd – 25th) and cessation dates on the second dekade of December (i.e.10th -12th), indicating a maximum duration of 55- 60 days and makes a cycle of the short rains. The atmospheric circulation anomalies of SST, Winds, Relative Humidity and Vertical Velocity during wet years are linked with low level unstable moist winds originated from Congo basin. These anomalies are organized and converges with maritime north easterly winds from the Indian Ocean (mostly over the northern coast of Tanzania, including Zanzibar) and becoming a potential cause for rainfall during the season, while during dry years, the winds diverge as a result of dryness over the region. Therefore the results indicates that convergence (divergence) of the northwesterly to westerly, easterly and southeasterly flow contributed to the early(late) wetness (dryness) over Zanzibar and its surroundings. The study results will help to enhance the improvement of short rains seasonal onsets and cessations forecasts and improve the socio - economic activities over Zanzibar and Tanzanian at large.